Reciprocal associations between affectual, associational, and normative solidarity with parents during children's early to established adulthood. Issue 3 (23rd September 2021) - Hwang, Woosang; Kim, Jeung Hyun; Cheng, Kent Jason; Brown, Maria T.; Silverstein, Merril
Abstract: Intergenerational solidarity has become increasingly important to understand, as close family members mobilize the provision of social support across generations and contribute to family wellbeing. However, less is known about continuity and change in normative (eldercare norms), affectual, and associational solidarity with mothers and fathers as children emerge into full or established adulthood. Therefore, we focused on reciprocal associations between three dimensions of intergenerational solidarity (normative, affectual, and associational) as reported by young‐adult children from their early twenties to late thirties. Data were derived from respondents in the Longitudinal Study of Generations: daughters reported about relationships with 291 mother–father pairs and sons reported about relationships with 309 mother–father pairs in 2000, 2005, and 2016. Autoregressive cross‐lagged models prospectively predicted mutual influences among the three dimensions of solidarity across daughter‐parent and son‐parent relationships. In addition, multiple group analysis was conducted to examine the children's gender difference. We found that normative solidarity and emotional closeness with mothers were mutually reinforcing in daughters' and sons' parental relationships. However, normative solidarity predicted emotional closeness with fathers in both daughter‐parent and son‐parent relationships. The study concludes that sons and daughters establish eldercare norms based on emotional components of solidarity with mothers, and suggest that filial duty is a key reason why mother‐child relations become close over the family life course. Resumen: La solidaridad intergeneracional se ha vuelto cada vez más importante de comprender, ya que los familiares cercanos movilizan el apoyo social entre las generaciones y contribuyen al bienestar familiar. Sin embargo, se sabe poco acerca de la continuidad y el cambio en la solidaridad normativa (las normas de cuidado de los adultos mayores), afectiva y asociativa con las madres y los padres a medida que los hijos entran en la adultez completa o definitiva. Por lo tanto, nos centramos en las asociaciones recíprocas entre las tres dimensiones de solidaridad intergeneracional (normativa, afectiva y asociativa) según lo informado por los hijos jóvenes‐adultos desde sus veinte hasta sus cuarenta años. Los datos se tomaron de personas encuestadas en el Estudio Longitudinal de Generaciones: las hijas informaron acerca de las relaciones con 291 pares de madres y padres y los hijos informaron acerca de las relaciones con 309 pares de madres y padres en los años 2000, 2005 y 2016. Los modelos autorregresivos de retardo cruzado predijeron prospectivamente influencias mutuas entre las tres dimensiones de solidaridad en las relaciones entre la hija y el padre/la madre y las relaciones entre el hijo y el padre/la madre. Además, se realizaron análisis multigrupo para analizar la diferencia de género de los hijos. Descubrimos que la solidaridad normativa y la cercanía emocional con las madres se reforzaron mutuamente en las relaciones parentales de las hijas y los hijos. Sin embargo, la solidaridad normativa predijo la cercanía emocional con los padres tanto en las relaciones entre la hija y el padre/la madre como en las relaciones entre el hijo y el padre/la madre. En el estudio se llega a la conclusión de que los hijos y las hijas establecen normas de cuidado de los adultos mayores basándose en los componentes emocionales de la solidaridad con las madres, y se sugiere que el deber filial es un motivo clave por el cual las relaciones entre madre e hijos se vuelven cercanas durante el transcurso de la vida familiar. 摘要: 理解代际之间的团结已变得越来越重要，因为亲近的家庭成员推动了跨代提供社会支持，有助于大小家庭的福祉。然而，当孩子进入正式的成年期或完全稳定的成年期时，人们对约定俗成的(老年护理规范)、情感和与父母的关联地团结的连续性和变化知之甚少。因此，我们关注的是由20岁出头到30岁后期的年轻人报告的代际团结的三个方面(社会道义、情感和联想)之间的相互关联。来自代际纵向研究的受访者的数据: 2000年、2005年和2016年，女儿报告了与291对父‐母的关系，儿子报告了309对父‐母的关系。自回归交叉滞后模型预测了代际团结的三个维度之间的在女儿‐父母和儿子‐父母关系的相互影响。此外，通过多组分析，探讨孩子们性别上的差异。笔者发现，在女儿和儿子的父母关系中，道义上的的团结和与母亲的情感亲近是相互加强的。然而，无论是在父子关系中还是在母女关系中，道义上的的团结都预示着与父亲的情感亲近。该研究得出结论，儿子和女儿在与母亲团结的情感成分的基础上建立了照顾老人的规范，并表明孝道责任是家庭生活过程中母子关系变得亲密的一个关键原因。